A kiskereskedelem terei Győrben - Nagy, Erika (Tér és Társadalom, 1996)
In the early 90'-es the trade was the most attractive economic sector for the investors in ungary or the foreigners. The number of actors were multiplied, and paralell with this rocess there was a constitutional change, too. The most important centres of this transformation were the big cities, especially the holesale trade division centres. In there cities with their population, area, and special nctions can give us a chance to analyse the changes of the trade sector, e.g. the spatial tructure, the hierarchy of the retail trade and service centres, and the movements inside he city. This spatial structure and this hierarchy can be analysed only an empiric way, because he detailed business and property catasteres are missing. So, if we are able to collect the ost important and the smaller clusters, and we can specify the structural characters of hem, we have a chance to form a real picture of the inner structure of the city.